Design and Development of Yellow Watermelon Juice Packaging - TEOH, SHERLYN XUE NING; Shaiful Rizal Masrol; Norsahidah Abdullah; Mohamad Firdaus Saat (Progress in Engineering Application and Technology, 2024)
This project focuses on developing yellow watermelon juice, emphasizing efficient processing and suitable packaging to extend its shelf life and reduce transportation and storage costs. Yellow watermelon juice is valued for its refreshing flavor but faces challenges such as short shelf life, limiting its year-round availability. The research aims to design, prototype, and evaluate consumer satisfaction with both the taste and packaging of the juice. The scope includes consumer surveys, juice processing, sensory tests, the use of PET bottles, and detailed labeling. Customer satisfaction surveys help understand consumer preferences in packaging. The development process involves creating informative labels to meet customer needs. High-temperature pasteurization methods ensure the juice retains its nutritional value and sensory properties while extending shelf life. The project also highlights the importance of eco-friendly packaging, with PET bottles preferred for their lightweight, recyclable, and convenient properties. PET bottles successfully passed drop testing using the ASTM D2463 standard, ensuring durability during handling, transportation, and storage. Conclusion, the project successfully develops yellow watermelon juice in PET bottle packaging, focusing on consumer acceptance.This project focuses on developing yellow watermelon juice, emphasizing efficient processing and suitable packaging to extend its shelf life and reduce transportation and storage costs. Yellow watermelon juice is valued for its refreshing flavor but faces challenges such as short shelf life, limiting its year-round availability. The research aims to design, prototype, and evaluate consumer satisfaction with both the taste and packaging of the juice. The scope includes consumer surveys, juice processing, sensory tests, the use of PET bottles, and detailed labeling. Customer satisfaction surveys help understand consumer preferences in packaging. The development process involves creating informative labels to meet customer needs. High-temperature pasteurization methods ensure the juice retains its nutritional value and sensory properties while extending shelf life. The project also highlights the importance of eco-friendly packaging, with PET bottles preferred for their lightweight, recyclable, and convenient properties. PET bottles successfully passed drop testing using the ASTM D2463 standard, ensuring durability during handling, transportation, and storage. Conclusion, the project successfully develops yellow watermelon juice in PET bottle packaging, focusing on consumer acceptance.